A Revised Supply Block for the Major Seven Countries in INTERLINK - Jarrett, Peter (OECD Economics Department Working Papers, 1987)
While the philosophy behind the supply block has not changed since its initial version, each of the block's behavioural equations as well as the parameters of the production functions have been substantially modified. These modifications have been motivated, in general, by a wish to improve the consistency of the block and to relax some of the constraints imposed. Consistency has been improved via a minor modification to the procedure for estimating the parameters of the production function, as well as from the inclusion of a measure of "normal" inventory growth in the demand term in the output equation. In the new version, the equilibrium stock/output ratio is no longer treated as a constant; tax considerations and domestic price effects are now included in the business energy price equations, and the dynamic adjustment of the factor demand equations has been made more general. Finally, some research on potential output, based on the revised production model, is reported ...